α-Synuclein disrupts microglial autophagy through STAT1-dependent suppression of Ulk1 transcription - Chong-Shuang Pei; Xiao-Ou Hou; Zhen-Yuan Ma; Hai-Yue Tu; Hai-Chun Qian; Yang Li; Kai Li; Chun-Feng Liu; Liang Ouyang; Jun-Yi Liu; Li-Fang Hu (Journal of Neuroinflammation, 2024)
Abstract Background Autophagy dysfunction in glial cells is implicated in the pathogenesis of Parkinson’s disease (PD). The previous study reported that α-synuclein (α-Syn) disrupted autophagy in cultured microglia. However, the mechanism of microglial autophagy dysregulation is poorly understood. Methods Two α-Syn-based PD models were generated via AAV-mediated α-Syn delivery into the mouse substantia nigra and striatal α-Syn preformed fibril (PFF) injection. The levels of microglial UNC-51-like kinase 1 (Ulk1) and other autophagy-related genes in vitro and in PD mice, as well as in the peripheral blood mononuclear cells of PD patients and healthy controls, were determined via quantitative PCR, western blotting and immunostaining. The regulatory effect of signal transducer and activator of transcription 1 (STAT1) on Ulk1 transcription was determined via a luciferase reporter assay and other biochemical studies and was verified through Stat1 knockdown or overexpression. The effect of α-Syn on glial STAT1 activation was assessed by immunohistochemistry and western blotting. Changes in microglial status, proinflammatory molecule expression and dopaminergic neuron loss in the nigrostriatum of PD and control mice following microglial Stat1 conditional knockout (cKO) or treatment with the ULK1 activator BL-918 were evaluated by immunostaining and western blotting. Motor behaviors were determined via open field tests, rotarod tests and balance beam crossing. Results The transcription of microglial ULK1, a kinase that controls autophagy initiation, decreased in both in vitro and in vivo PD mouse models. STAT1 plays a critical role in suppressing Ulk1 transcription. Specifically, Stat1 overexpression downregulated Ulk1 transcription, while Stat1 knockdown increased ULK1 expression, along with an increase in LC3II and a decrease in the SQSTM1/p62 protein. α-Syn PFF caused toll-like receptor 4-dependent activation of STAT1 in microglia. Ablation of Stat1 alleviated the decrease in microglial ULK1 expression and disruption of autophagy caused by α-Syn PFF. Importantly, the ULK1 activator BL-918 and microglial Stat1 cKO attenuated neuroinflammation, dopaminergic neuronal damage and motor defects in PD models. Conclusions These findings reveal a novel mechanism by which α-Syn impairs microglial autophagy and indicate that targeting STAT1 or ULK1 may be a therapeutic strategy for PD.